Increased protein and mRNA expression of corticotropin-releasing factor (CRF), decreased CRF receptors and CRF binding protein in specific postmortem brain areas of teenage suicide subjects - Pandey, Ghanshyam N.; Rizavi, Hooriyah S.; Bhaumik, Runa; Ren, Xinguo (Psychoneuroendocrinology, 2019)
•Abnormalities of HPA-axis are associated with depression and suicidal behavior.•CRF expression is increased in PFC, but not in HIPPO of teenage suicide subjects.•We found region-specific changes in the expression of CRF and its receptors.•Increased CRF and decreased CRF-BP and CRF-R1 may be associated with suicide. Overactivity of hypothalamic-pituitary-adrenal (HPA) axis function has been implicated in depression and suicidal behavior. This is based on the observation of an abnormal dexamethasone (DEX) and DEX-adrenocorticotropic hormone (ACTH) test in patients with depression and suicidal behavior. Recently, some studies have also found abnormalities of glucocorticoid receptors (GR), mineralocorticoid receptors (MR), corticotropin releasing factor (CRF), CRF receptors (CRF-R) and CRF binding protein (CRF-BP) in depressed and suicidal patients. Some investigators have also observed increased levels of CRF in the cerebrospinal fluid (CSF) and altered levels of MR, GR and CRF in the postmortem brain of depressed and suicidal subjects. We have earlier reported decreased protein and mRNA expression of GR and GILZ, a chaperone protein, in the postmortem brain of teenage suicide subjects. We have further studied CRF and its receptors in different areas of the postmortem brain of suicide subjects, i.e., the prefrontal cortex (PFC), hippocampus (HIPPO), subiculum and amygdala (AMY) from teenage suicide subjects. The CRF and its receptors were determined in the PFC (Brodmann area 9), HIPPO, subiculum and different amygdaloid nuclei from 24 normal control subjects and 24 teenage suicide subjects. Protein expression of CRF, its receptors and CRF-BP was determined by immunolabeling using the Western blot technique and mRNA expression was determined by real-time PCR (qPCR) technique. We found that the mRNA levels of CRF were significantly increased in the PFC, in the central amygdaloid nucleus (CeAMY) and in the subiculum. mRNA levels of CRF-R1 and CRF-BP were significantly decreased in the PFC. We did not find any changes in the HIPPO of any of the CRF components we studied. When we compared the protein expression of CRF components we found that CRF was significantly increased and CRF-R1, CRF-R2 and CRF-BP significantly decreased in the PFC. On the other hand, there were no changes in the protein expression of CRF components in the HIPPO. Our results in the postmortem brain suggest that, as found by clinical studies in the CSF, there are significant alterations of CRF and its receptors in the postmortem brain of teenage suicide subjects. These alterations of CRF and its components were region-specific, as changes were not generally observed in the HIPPO.